Effect of WFH Implementation on Employee Performance; with Work Motivation and Job Satisfaction as Mediation Variables and Information Technology Capability as Moderating Variables (Study on Administrative Employees of Universitas Brawijaya) - Virdani, Rachel Nitrogena; Noermijati, Noermijati; Hadiwidjojo, Djumilah (Journal of Social Research, 2023)
The coronavirus disease (COVID-19) pandemic, which spread from March 2020 to April 2022, is very concerning. The government is making various efforts to reduce the spread of the virus, including implementing "social distancing" by limiting visits to crowded places and direct contact with other people. One of the methods used to implement social distancing is through working from home or "Work From Home" (WFH). This study aims to empirically test and prove the effect of WFH on employee performance where the variables of employee motivation and job satisfaction act as mediating variables and information technology capability variables as moderating variables. This research is a quantitative study with individual analysis units on 221 administrative staff from each faculty at Universitas Brawijaya through distributing questionnaires. The number of returned questionnaires was 95%. The data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The results of the study found that: WFH has no direct effect on employee performance; WFH affects employee performance as Employee Job Satisfaction is mediation; Employee Motivation does not mediate the effect of WFH on Employee Performance; also IT Capability does not moderate the effect of WFH on Employee Performance.